Geography, environment, and colonization history interact with morph type to shape genomic variation in an Arctic fish ... - Salisbury, Sarah J.; Perry, Robert; Keefe, Donald; McCracken, Gregory R.; Layton, Kara K. S.; Kess, Tony; Bradbury, Ian R.; Ruzzante, Daniel E. (Dryad, 2022)
Polymorphic species are useful models for investigating the evolutionary processes driving diversification. Such processes include colonization history as well as contemporary selection, gene flow, and genetic drift, which can vary between intraspecific morphs as a function of their distinct life histories. The interactive and relative influence of such evolutionary processes on morph differentiation critically informs morph-specific management decisions and our understanding of incipient speciation. We therefore investigated how geographic distance, environmental conditions, and colonization history interacted with morph migratory capacity in the highly polymorphic fish species, Arctic Charr (Salvelinus alpinus). Using an 87k SNP chip we genetically characterized recently evolved anadromous, resident, and landlocked charr collected from 45 locations across a secondary contact zone of three charr glacial lineages in eastern Canada. A strong pattern of isolation by distance across all populations suggested ...